Qsar study on glutathione s-transferase inhibitors - Ohanoğlu, Linda (My University, 2014)
GLUTATYON S-TRANSFERAZ ENZİMİ İNHİBİTÖRLERİ İLE QSAR ÇALIŞMASI Glutatyon S-transferaz (GST) hücreyi sitotoksik ve genotoksik streslerden koruyan çok işlevli bir enzimdir. GST P1-1 enziminin birçok fonksiyonu vardır ve bu fonksiyonlar arasında kanser tedavisinde kullanılan ilaçları etkisiz hale getirdiği bilinmektedir. Etakrinik asit (EA) tümör hücrelerinde zayıf antiproliferatif bir GST P1-1 inhibitörü olarak bilinmektedir. Yakın bir zamanda EA türevi olan 28 heterosiklik okzadiazol bileşiğinin GST P1-1 inhibisyon aktivitesi raporlanmıştır ve bu türevler yeni bir sınıf antitümör adayları olarak gösterilmiştir. Bu çalışmada, bahsi geçen bileşiklerin GST P1-1 inhibisyon aktivitelerini gösteren pIC50 değerleri kullanılarak Çoklu Doğrusal Regresyon (MLR) yöntemi ile Kantitatif Yapı-Aktivite (QSAR) modelleri ile oluşturuldu. Moleküler tanımlayıcılar DRAGON 6.0 yazılımı ile hesaplandı. Veri seti %75 çalışma ve % 25 test seti olarak ayrıldı. İki-tanımlayıcılı 8 adet QSAR modeli QSARINS kullanılarak geliştirildi. Tüm modellerin içsel ve dışsal validasyonları yapıldı. Modellerde uygulama alanının dışına sapan hiçbir bileşik bulunmadı. Elde edilen 8 model içersinde, en iyi modelin parametreleri; R2= 0.8019 R2adj= 0.7799 and RMSEtr=0.1089, test setin istatiksel parametreleri ise R2ext=0.8702 RMSEext=0.1086 and CCCext=0.8916’dir. Bu değerler modelin test seti iyi tahmin edebilir nitelikte olduğunu göstermektedir. Elde edilen modeler arasında 2D otokorelasyon tanımlayıcısı en baskın tanımlayıcı olarak görüldü. Seçilen en iyi model kullanılarak yeni 4 adet umut vaat eden GST inhibitörü EA okzadiazol türevi tasarlanmıştır.

QSAR STUDY ON GLUTATHIONE S-TRANSFERASE INHIBITORS Glutathione S-transferases (GSTs) are a polymorphic superfamily of multifunctional enzymes that protect cells from cytotoxic and genotoxic stresses. GST P1-1, owing to its multiple functions, is considered as a target for developing therapeutic agents for cancer treatment in regulating multidrug resistance, cell proliferation, and apoptosis. Ethacrynic acid (EA) is known as a GST P1-1 inhibitor with weak antiproliferative ability in tumor cells. GST P1-1 inhibitory activities of 28 novel EA derivatives containing heterocyclic oxadiazole rings were recently reported, representing a new group of antitumor candidates. In this study, 8 QSAR models were developed based on the GST P1-1 inhibitory concentration (pIC50) of 28 EA oxadiazole derivatives. The descriptors were calculated from geometry optimized 3-D structures using Dragon 6 software package. Data set was divided into training (75%) and test sets (25%) randomly. 8 two-descriptor multiple linear regression (MLR) models with no structural and response outliers were developed using QSARINS 1.1 software. All models were validated internally and externally. Of the 8 generated models, the selected model having the best statistical fit and predicting ability has R2= 0.8019 R2adj= 0.7799 and RMSEtr=0.1089. The statistical parameters of test set are R2ext=0.8702, RMSEext=0.1086 and CCCext=0.8916 reflectingavery good predictive power for the test set. The variable that was most closely correlated with the inhibitory activity is the 2D autocorrelation descriptor, reflecting the importance of molecular branching and complexicity in the inhibitory activity of EA oxidazole derivatives. Using the developed model, we designed 4 new EA oxadiazole derivatives exhibiting promising GST inhibitory activity.
Keywords: Kimya, Organik